2018
DOI: 10.1007/s10549-017-4638-1
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variants demonstrating flip-flop phenomenon and breast cancer risk prediction among women of African ancestry

Abstract: We found that PRS based on variants identified from prior GWASs conducted in women of European and Asian ancestries did not provide a comparable degree of risk stratification for women of African ancestry. Further large-scale fine-mapping studies in African ancestry populations are desirable to discover population-specific genetic risk variants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(60 citation statements)
references
References 30 publications
4
56
0
Order By: Relevance
“…Previous studies on breast cancer found that risk stratification models could perform differently for patients with various family histories of tumor. 41 , 42 Familial risks could reflect the shared genetic susceptibility and similar exposures to environmental risk factors and have been reported to be associated with esophageal carcinogenesis and prognosis. 43 Patients could benefit from risk evaluation that involves collection of detailed information on clinical risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on breast cancer found that risk stratification models could perform differently for patients with various family histories of tumor. 41 , 42 Familial risks could reflect the shared genetic susceptibility and similar exposures to environmental risk factors and have been reported to be associated with esophageal carcinogenesis and prognosis. 43 Patients could benefit from risk evaluation that involves collection of detailed information on clinical risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence is accumulating that relying solely on populations of European descent results in an incomplete or inaccurate representation of the genetic susceptibility to cancers (27). For example, replication of risk loci found in European populations through GWAS in multiethnic cohorts has revealed that risk factors may differ in their nature and magnitude of effect (33). The recent increases in the inclusion of non-European populations in GWAS has been mostly attributed to an increase in representation of Asian populations and collectively, African, Hispanics/Latinos, and native or indigenous populations represented less than 4% of the 35 million samples included in 2,500 studies reported in the GWAS catalog (34).…”
Section: Limited Cancer Research In Diverse Populationsmentioning
confidence: 99%
“…Interestingly, a Latina breast cancer GWAS identified a protective variant of Indigenous American origin at the 6q25 locus, which acts independently of the previously known risk variants at this locus (50). Thus, variants associated with risk may not validate in other populations, or even change the direction of risk association (33). Importantly, polygenic risk scores for stratifying women based on their inherited risk of developing breast cancer, which have been developed using data derived largely from European population GWAS, perform poorly in African-American populations as a consequence of inverse directionality of 30%-40% of the susceptibility loci (33).…”
Section: Ancestral-related Health Disparities In Cancer: Breast Cancermentioning
confidence: 99%
“…Genomic studies conducted in large AA and/or multi-ethnic cohorts have begun to utilize modified genomic tools in search of population-specific risk alleles. SNVs, structural, chromosomal, and epigenetic variations are being discovered and associated with a still theoretical genetic predisposition for the distinct tumor biology observed among women of West African descent (40)(41)(42)(43). While more risk alleles are being detected through increased diversity of multi-ethnic genome-wide association study (GWAS), the specific risk alleles transmitted into non-white populations through African genetic ancestry have not yet been definitively shown (44).…”
Section: Distinct Tumor Immune Responses Among Ancestry Groups With Cmentioning
confidence: 99%